Community Mobilization for Youth Health Promotion: A Lesson Learned From Iran - Sh Djalalinia; F Ramezani Tehrani; H Malek Afzali; N Peykari; M Baradaran Eftekhari (Tehran University of Medical Sciences, 2012)
Background: More than 36 % of the total population of Iran consists of young people aged 15 to 25 yr. Recent studies show that this age group has the highest rate of serious health problems. Youth participatory studies on youth health priority have shown that mental health is one of the most important priorities in youth health. Aim to assessing the mental health needs of youth we conducted a peer group based multidisciplinary study. Methods: To conduct a multi disciplinary approach through involving youth for finding their mental health needs and their suggestion for solving them, we designed a qualitative approach based on grounded theory. To data collection, we used a semi-structured guide questionnaire. Sixteen focus group discussions were conducted by trained peers with youth aged 15-25 years. Result: According to FGDs results, most of youth health needs concern with their interpersonal communications skills particularly with their parents'; they had some problems with their parental expectations meet; life skills; self-expression and problem solving process. They were extremely interested in participatory approach in which they involved in assessment and determination of their health problems also in designing health programs. Conclusion: Success of program shows empowering the community through capacity building and notice to peer group-based interventions to critical enhancing in various aspects of youth health is the most effective method to needs assessment and community mobilization for better health.